The effect of external ankle support on knee joint biomechanics during sporting tasks - Bronn, Karla (Stellenbosch : Stellenbosch University, 2025)
Bronn, K. 2025. The Effect of External Ankle Support on Knee Joint Biomechanics During Sporting Tasks. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/d4f241ca-78e7-492d-897c-152e2c2ba45a